Patient and illness factors influencing fear of recurrence in breast cancer women - Supriati, Lilik; Sudiana, Ketut; Nihayati, Hanik Endang; Ahsan; Rodli, Muhammad; Kapti, Rinik Eko (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the factors influencing the fear of recurrence in breast cancer, including age, spirituality, length of illness, stage of cancer and the cycles of chemotherapy. Method: The cross-sectional observational study was conducted from November 2021 to February 2022 at Dr Soepraoen Army Hospital and Baptis Hospital, East Java, Indonesia, and comprised breast cancer patients who had received at least one cycle of chemotherapy. Data was collected using the modified Spiritual Transcendence Scale questionnaire as well as from the patient’s medical record. Data were analysed using univariate and linear regression. Results: There were 135 subjects with a mean age of 47.14±6.36 years (range: 27-60 years). The largest group comprised patients with stage III disease 61(45.2%). Variables affecting the fear of recurrence was length of illness (p=0,007) and spirituality (p=0,001). Conclusion: Patients who had better spirituality value had lower fear of recurrence. Keywords: Spirituality, Fear, Breast neoplasms, Medical records.